PEMBERDAYAAN KADER LANSIA DALAM PENCEGAHAN DIABETES DI BANJAR TEGAL SUCI, TEGALALANG, GIANYAR - Dewi, Sri Ratna; Sudiarta, I Wayan; Pradnyadari, Luh Made Ayu (JURNAL SEWAKA BHAKTI, 2025)
Banjar Tegal Suci in Sebatu Village, Tegalallang, Gianyar, is one of the banjars with a relatively high number of elderly residents. Although there is already an elderly group and cadres, the activities carried out are still limited, such as the lack of diabetes screening, low health insurance coverage, and insufficient knowledge about healthy food preparation. The objective of this Community Partnership Program (PkM) is to improve the knowledge and quality of life of the elderly through several steps, namely diabetes screening, health insurance education, and education on diabetes prevention and healthy food preparation. The problem-solving framework applied includes three main steps: 1) Conducting diabetes screening by checking blood glucose levels, 2) Providing an understanding of the benefits of health insurance, how to register, and conducting meetings with relevant parties, and 3) Organizing education on diabetes prevention, healthy food preparation, and elderly exercise. The PkM activities were carried out in stages, starting with socialization to stakeholders and followed by the implementation of diabetes screening and education. The results showed an increase in knowledge among the cadres and the elderly, with a recorded 84% improvement in pre- and post-test scores for the cadres. Blood glucose testing revealed that 3 elderly individuals had glucose levels >200 mg/dL, and they were advised to follow up with further examinations. Additionally, to increase motivation, glucometers, weight scales, and t-shirts were provided to the cadres and the Puskesmas. Based on the results of these activities, it can be concluded that the PkM has successfully improved the elderly's knowledge and awareness of their health, particularly in diabetes prevention, and has improved access to healthcare services through health insurance.